CRIME IN OPEN PUBLIC SPACES IN THE POST-SOVIET CITIES: LITHUANIAN CASE - Matijosaitiene, Irina; Zaleckis, Kestutis (European Scientific Journal, ESJ, 2014)
From the spatial social point of view a city can be represented as a sequence of connected or disconnected open public spaces. Open public spaces (streets, squares, parks, yards etc.) can be treated as the social infrastructure of the city through which people move, where they meet, communicate and act. Even in ancient times open public spaces were used not only as people gathering places, fair or fiesta spaces, but also various shows and gambling took place on public spaces as well delinquent people were nailed to shame poles. The importance of public spaces for city dwellers and city guests is obvious. Human behavior in open public spaces can be described though movement in the spaces. The intensity and character of movement, assessed by using the space syntax method, enable us to identify the most easy/hardly accessible spaces (integration values), spaces which are the most/least likely to be passed through (choice values), and the most deep/shallow spaces (depth values). These and other social spatial characteristics of urban space are applied for the research of behaviour of city dwellers and city guests. This stage of the research revealed that some public spaces were safer than others. The authors seek to identify how urban spatial structure correlates with and impacts urban crime. As a research object ten largest Lithuanian cities were selected. All of them represent a Post-Soviet case of urban development. The results allow us to understand the dependencies of particular types of crime and spatial social structure of cities.